Aromatase Deficiency in Two Siblings with 46,XX Karyotype Raised as Different Genders: A Novel Mutation (p.R115X) in the CYP19A1 Gene - Samim Özen; Tahir Atik; Özlem Korkmaz; Hüseyin Onay; Damla Gökşen; Ferda Özkınay; Özgür Çoğulu; Şükran Darcan (Galenos Yayincilik, 2020)
Aromatase deficiency rarely causes a 46,XX sexual differentiation disorder. The CYP19A1 gene encodes the aromatase enzyme which catalyses the conversion of androgens to oestrogens. In cases with 46,XX karyotype, mutations in the CYP19A1 gene can lead to disorders of sex development. Clinical findings in aromatase deficiency vary depending on the degree of deficiency. The effect of increased androgens, including acne, cliteromegaly and hirsutism, can be observed in mothers with placental aromatase deficiency. A decrease in maternal virilisation symptoms is observable in the postpartum period. It is rarely reported that there is no virilization in pregnancy. In this study, two 46,XX sibling having the p.R115X (c.343 C>T) novel pathogenic variant in the CYP19A1 gene and raised as different genders, with no maternal virilisation during pregnancy, are presented. In conclusion, 46,XX virilised females should be examined in terms of aromatase deficiency once congenital adrenal hyperplasia has been excluded, even if there is no history of maternal virilisation during pregnancy.